Integration of Routine Parameters of Glycemic Variability in a Simple Screening Method for Partial Remission in Children with Type 1 Diabetes - Nina Nielens; Olivier Pollé; Annie Robert; Philippe A. Lysy (Journal of Diabetes Research)
Although different criteria were used to define partial remission in type 1 diabetes, the IDAA1C formula has prevailed as it correlates with stimulated C-peptide levels. Our retrospective study evaluated clinical variables associated with the occurrence of IDAA1C-defined partial remission in a series of 239 pediatric patients. Diabetic ketoacidosis and age at diagnosis, but no other clinical feature, influenced the occurrence of remission. We then evaluated whether parameters of glycemic variability used in clinical routine may reliably define partial remission, as these would alleviate confounding factors related to insulin treatment. Using multiple linear regression, we observed that HbA1C levels and percentage of normoglycemia were efficient and sufficient to predict partial remission. These parameters were entered into a formula, called glycemic target-adjusted HbA1C (GTAA1C), that corresponded to HbA1C(%) − (3 × % of normoglycemic values(70–180 mg/dL)). With a threshold of 4.5, this alternative formula predicted partial remission with a sensitivity and a specificity of 72.3% and 92%, respectively, and yielded strong correlation with IDAA1C levels and BETA-2 score, which is a correlate of β-cell function after islet transplantation. We propose GTAA1C, based on routine and objective markers of glycemic variability, as a valid alternative for definition of partial remission in type 1 diabetes.